Current Perspectives on the Beneficial Effects of Soybean Isoflavones and Their Metabolites for Humans - Il-Sup Kim (MDPI AG, 2021)
Soybeans are rich in proteins and lipids and have become a staple part of the human diet. Besides their nutritional excellence, they have also been shown to contain various functional components, including isoflavones, and have consequently received increasing attention as a functional food item. Isoflavones are structurally similar to 17-β-estradiol and bind to estrogen receptors (ERα and ERβ). The estrogenic activity of isoflavones ranges from a hundredth to a thousandth of that of estrogen itself. Isoflavones play a role in regulating the effects of estrogen in the human body, depending on the situation. Thus, when estrogen is insufficient, isoflavones perform the functions of estrogen, and when estrogen is excessive, isoflavones block the estrogen receptors to which estrogen binds, thus acting as an estrogen antagonist. In particular, estrogen antagonistic activity is important in the breast, endometrium, and prostate, and such antagonistic activity suppresses cancer occurrence. Genistein, an isoflavone, has cancer-suppressing effects on estrogen receptor-positive (ER+) cancers, including breast cancer. It suppresses the function of enzymes such as tyrosine protein kinase, mitogen-activated kinase, and DNA polymerase II, thus inhibiting cell proliferation and inducing apoptosis. Genistein is the most biologically active and potent isoflavone candidate for cancer prevention. Furthermore, among the various physiological functions of isoflavones, they are best known for their antioxidant activities. S-Equol, a metabolite of genistein and daidzein, has strong antioxidative effects; however, the ability to metabolize daidzein into S-equol varies based on racial and individual differences. The antioxidant activity of isoflavones may be effective in preventing dementia by inhibiting the phosphorylation of Alzheimer's-related tau proteins. Genistein also reduces allergic responses by limiting the expression of mast cell IgE receptors, which are involved in allergic responses. In addition, they have been known to prevent and treat various diseases, including cardiovascular diseases, metabolic syndromes, osteoporosis, diabetes, brain-related diseases, high blood pressure, hyperlipidemia, obesity, and inflammation. Further, it also has positive effects on menstrual irregularity in non-menopausal women and relieving menopausal symptoms in middle-aged women. Recently, soybean consumption has shown steep increasing trend in Western countries where the intake was previously only 1/20-1/50 of that in Asian countries. In this review, Ihave dealt with the latest research trends that have shown substantial interest in the biological efficacy of isoflavones in humans and plants, and their related mechanisms.